Peningkatan Program Bina Pribadi Islam di SMA Islam Terpadu Granada Samarinda - Muhammad Hendrie Fauzan (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2020)
In this era, there are changes in the behavior of the younger generation. Many students are engaging in promiscuity, smoking, consuming alcoholic, bullying, and using prohibited drugs. School efforts are needed to changes these negative behavioral. One of effort is through the Islamic personal development program. This Islamic development program emphasizes on Nurturing. Development, etymologically derived from the Arabic language